Effectiveness of Science-Technology-Society (STS) Instruction on Student Understanding of the Nature of Science and Attitudes toward Science - Akcay, Behiye; Akcay, Hakan (NECMETTIN ERBAKAN UNIV, 2015)
The study reports on an investigation about the impact of science-technology-society (STS) instruction on middle school student understanding of the nature of science (NOS) and attitudes toward science compared to students taught by the same teacher using traditional textbook-oriented instruction. Eight lead teachers used STS instruction an attempt to improve student understanding of NOS concepts. The major findings of the study suggest that students experiencing STS instruction improve their understanding of the nature of science and attitudes toward science significantly more than do students who were instructed with traditional instruction. Analysis of the data indicates that students in STS classrooms attain more positive changes in their views about the NOS. Specifically, the STS students displayed powerful changes in their understanding of the ways in scientific theories and the scientist. Implications for improving teacher professional development programs are suggested.
Keywords: Attitude toward science; Nature of science; Science-Technology-Society (STS); Science education; Education & Educational Research